Pengaruh Kepadatan Dan Size Ikan Terhadap Sintasan Benih Ikan Nila (Oreochromis Niloticus) Pada Pengangkutan Sistem Semi Terbuka - Dewa Gede Semara Edi; Sang Ayu Made Putri Suryani; Ketut Caraka Bagus Sewaka (GEMA AGRO, 2024)
Transportation of fish seeds is the best way to move fish seeds from farmers to buyers. Proper transportation of live tilapia fish can ensure that the fish remain alive, healthy and fresh until their destination. The aim of this research is to determine the effect of density and size on fish seed catch in tilapia seed transport and to determine the interaction between density and size on tilapia seed catch in semi-open transport. Research location: Transportation was carried out from the seed source at the tilapia hatchery business in Patas Village, Gerokgak District, Buleleng Regency and ended at the Mina Anakan Jepun Fish Cultivator Group, Bebetin Village, Sawan District, Buleleng Regency, Patas, Gerokgak District, Buleleng Regency, Bali. This research used a Completely Randomized Design (CRD) with a factorial pattern with 2 factors consisting of Factor 1, namely fish density consisting of 3 levels, namely 50 fish/liter, 75 fish/liter, and 100 fish/liter. Factor 2 is the size of the fish which consists of 3 levels, namely 5-6 cm, 7-8 cm, 9-10 cm. Based on the results of treatment research, the density of fish numbers and fish size showed a very significant influence (P<0.01) on the survival rate of tilapia fry during semi-open transportation. The interaction between fish density and fish size showed no significant effect (P>0.05) on the survival rate of tilapia fish seedlings. A fish density of 100 fish/liter and a fish size of 5-7 cm resulted in the highest survival of tilapia fry during semi-open transportation.